Flower-Insect Visitor Interaction: Study Case on Rhododendron inundatum Sleumer in Bali Botanic Garden - Farid Kuswantoro (Journal of Tropical Biodiversity and Biotechnology, 2017)
The Rhododendron-insect relationship was quite well studied in the northern hemisphere. However, information on the flower-insect relationship of the Indonesian Rhododendron was limited. This study aims to find the interaction between Rhododendron inundatum Sleumer collected in Bali Botanic Garden and its flower-visiting insect. The study was conducted by observing insect visitation to the flower of R. inundatum for 1 hour a day and repeated for nine days. Data analysis was conducted by calculating the Visitation Rate (VR) of each visitor taxa to determine its frequency. Study result showed that R. inundatum in Bali Botanic Garden was visited mainly by Chrysopa sp., as well as members of the Vespidae, Curculionidae, Muscidae, Drosophilidae, and Tephritidae. The result of this study was dissimilar with the previous study of white-flowered Rhododendron, which was mainly visited by moths.